Peningkatan Kualitas Mahasiswa Sebagai Calon Guru Melalui Praktik Pengalaman Lapangan Terpadu - Naufal Ilma (LP2M IAIN Sultan Amai Gorontalo, 2017)
Considering on the Indonesian Teacher and Lecturer Act, every Indonesian teacher needs to have a teacher certification. Indeed, it is a good opportunity as well as a challenge for every institute, which is conducting student for teacher training program, to have qualified graduates. As a prospective to be a qualified teacher, they must have four competencies concerning paedagogy, attitude, personal, and social. The question that may arise is â€œHow to have such competencies?â€ Of course, many ways can be done. However, improving the quality of teaching practicum is one of the many possibilities that can be considered. Integrated Student Community Service-Teaching Experience Practicum (PPLT) which is combining community service programme and teaching experience practicum itself that has been developed by Faculty of Science and Teaching Study at Institute of Islamic State (IAIN) Sultan Amai Gorontalo to have a better model of such teaching practicum. Being a new model, PPLT must be analized regularly and continuously to get a better quality of it. Infact, it has been evaluated annually by involving some principals or headmasters, students, lecturers, and the developer team of PPLT. There are many comments, suggestions, criticism, and questions of them that need to be analyzed. However, the three points such as the main reason for having PPLT, the long time periode needed, and the way how to developing it are really good points that need to be clarified. This paper is presented for giving information and answering such questions .